Karakter Kuantitatif dan Hubungan Kekerabatan Genotipe Padi (Oryza sativa L.) Beras Merah dan Beras Hitam yang Ditanam secara Gogo - A'yun, Amilia Qurota; Aryana, I Gusti Putu Muliarta; Sudika, I Wayan; Suliartini, Ni Wayan Sri; Fauzi, M. Taufik (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
This study aims to determine the appearance of quantitative characters and kinship relationships of the genotype of red rice and black rice grown in gogo. The research was conducted in February – May 2024 on a medium plain land with an altitude of 370 meters above sea level, in Tampak Siring Village, Central Lombok, NTB. The materials used were 21 rice genotypes consisting of 11 red rice strains, 4 black rice strains, 2 red rice elders, 2 black rice elders and 2 comparison varieties (Inpago Unram I and IR64). The analysis used is the Analysis of Variance (ANOVA) of the Group Random Design (GRD) model with a real level of 5%, if there are real different characters, then the Duncan Multiple Range Test (DMRT) will be continued at a real level of 5%. Cluster analysis was carried out based on the average value of quantitative characters using the euclidean distance method using the R-Studio program. The results of the study showed that between strains all characters had different appearances except for the number of non-productive saplings. G-2 strain; G-6; and G-18 had the same results as Inpago Unram I. Kinship analysis conducted based on the average value of quantitative characters obtained four clusters, namely cluster I G-21, G-9, G-20, G-11, G-17; cluster II G-19, G-2, G-18, G-6, G-7; cluster III G-1, G-5, G-8, G10, G-3, G-4, G-16; and cluster IV G-12, G-15, G-13, G-14.